The Face of Business - Meyer I. Henry (Addison-Wesley Publishing Company, 1980)
Business, What is Business?, Business Management and Organization, Corporate Report Cards, Money Flow, Paying the Troops, Management and the Shareholders, The Corporation, Macro Organization, Staff Functions, Project Teams and Task Forces and Consultants, Top Management, People in Business, Training for Business, People, Benefits and Perquisites and Status Symbols, Tribal Mores and Taboos, Index.
Business, What is Business?, Business Management and Organization, Corporate Report Cards, Money Flow, Paying the Troops, Management and the Shareholders, The Corporation, Macro Organization, Staff Functions, Project Teams and Task Forces and Consultants, Top Management, People in Business, Training for Business, People, Benefits and Perquisites and Status Symbols, Tribal Mores and Taboos, Index.